Disruption of adaptor protein 2μ (AP‐2μ) in cochlear hair cells impairs vesicle reloading of synaptic release sites and hearing. (7th October 2015) - Jung, SangYong; Maritzen, Tanja; Wichmann, Carolin; Jing, Zhizi; Neef, Andreas; Revelo, Natalia H; Al‐Moyed, Hanan; Meese, Sandra; Wojcik, Sonja M; Panou, Iliana; Bulut, Haydar; Schu, Peter; et al.
Abstract: Active zones (AZs) of inner hair cells (IHCs) indefatigably release hundreds of vesicles per second, requiring each release site to reload vesicles at tens per second. Here, we report that the endocytic adaptor protein 2μ (AP‐2μ) is required for release site replenishment and hearing. We show that hair cell‐specific disruption of AP‐2μ slows IHC exocytosis immediately after fusion of the readily releasable pool of vesicles, despite normal abundance of membrane‐proximal vesicles and intact endocytic membrane retrieval. Sound‐driven postsynaptic spiking was reduced in a use‐dependent manner, and the altered interspike interval statistics suggested a slowed reloading of release sites. Sustained strong stimulation led to accumulation of endosome‐like vacuoles, fewer clathrin‐coated endocytic intermediates, and vesicle depletion of the membrane‐distal synaptic ribbon in AP‐2μ‐deficient IHCs, indicating a further role of AP‐2μ in clathrin‐dependent vesicle reformation on a timescale of many seconds. Finally, we show that AP‐2 sorts its IHC‐cargo otoferlin. We propose that binding of AP‐2 to otoferlin facilitates replenishment of release sites, for example, via speeding AZ clearance of exocytosed material, in addition to a role of AP‐2 in synaptic vesicle reformation. Synopsis: Active zones of sensory inner hair cells indefatigably release glutamate at very high rates. This study integrates experimental and theoretical approaches to indicate that the endocytic adaptor protein 2 (AP‐2) promotes vesicle replenishment possibly via facilitating the clearance of vesicular release sites. The study also shows a role of AP‐2 in synaptic vesicle reformation following bulk endocytosis. Hair cell‐specific deletion of AP‐2μ causes synaptic hearing impairment and hearing is rescued upon reinstating AP‐2μ expression via viral gene transfer. AP‐2μ is required for efficient vesicle replenishment at hair cell active zones. AP‐2μ likely facilitates the clearance of vesicular release sites from previously exocytosed material e.g. via binding to its cargo otoferlin. Synaptic vesicle formation following bulk endocytosis requires AP‐2μ. Abstract : The endocytic adaptor protein 2 (AP‐2μ) promotes synaptic vesicle replenishment by facilitating the clearance of vesicular release sites.